USING VOCABULARY GAMES IN ONLINE TEACHING ESP - Ishchuk, Nataliia; Shevchuk, Serhii (Collection of scientific papers «ΛΌГOΣ», 2022)
Introduction. Vocabulary is crucial when learning a language, whether it is your mother tongue or a foreign language. The four linguistic skills — listening, speaking, reading, and writing — should incorporate vocabulary. Students have to learn a great deal of words and know how to use them correctly in order to communicate effectively in a foreign language. The conventional approach to teaching vocabulary is rather monotonous. A teacher presents lexical units, asking students to record them in their notebooks, and ultimately learners have to memorize them before the following lesson. Besides, in terms of online learning, when students get tired of sitting in from of their monitors, some entertaining activities would definitely make the teaching-learning process more enjoyable for students.